Water quality parameters and nutrient status of selected reservoirs in Tamil Nadu, India - T. Deepak; P. Padmavathy; V. Rani; D. Manimekalai; Devasena, S. Subhashree (Indian Journal of Fisheries, 2022)
The present study was undertaken to assess the interrelation between water quality and nutrient status of three reservoirs situated in Tamil Nadu, India. These three reservoirs are managed by the Public Works Department (PWD) with the fisheries aspects falling under the purview of Tamil Nadu State Fisheries Department. In each reservoir, inflow and outflow sections were identified as sampling sites. A total of six sampling sites were fixed and monthly sampling for water and fish was conducted during the period from October 2019 to June 2020. The various physico-chemical parameters such as temperature, electrical conductivity (EC), total dissolved solids (TDS), total suspended solids (TSS), total volatile solids (TVS), turbidity, DO, pH, alkalinity, hardness, chloride, sulphate, biological oxygen demand (BOD) and chemical oxygen demand (COD) were analysed. Biological parameters like chlorophyll-a and primary production as well as various nutrient parameters were also analysed in the collected water samples. All the physical and chemical water quality variables showed significant variation (p<0.05) in their concentrations within various months and between stations. All the water quality parameters were observed to be within the prescribed limits. The results indicated under-exploitation of fishes from the reservoirs and suggest ways to improve fish yields and livelihood of local fisher community. Keywords: Fish catch, Nutrients, Reservoir, Water quality